Mallanca: A Manifestation of Community Joy at the Harvest Festival in Ajang Pulu Village, Bone Regency - Rahman, Abdul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine perceptions, values ​​and social changes in the implementation of the Mallanca tradition for the people of Belawae, Sibulue District, Bone Regency. This research uses observation, interviews and documentation methods. The results of the research show that the community considers that the Mallanca tradition is a tradition that has been passed down from generation to generation by the Belawae people which is deeply ingrained. Even though it was tough, there was no feeling of resentment between one player and another. Because it fosters ties of brotherhood and becomes a place for friendship. The noble cultural values ​​that are currently maintained by society can be sourced from social values, cultural values ​​and religious values. The changes that occur are basically only a few things that are material in nature. However, the spiritual aspect remains unchanged